Computation of ship responses in waves using panel method (Journal of Naval Architecture and Marine Engineering, 2009)
Hydrodynamic coefficients, Forces / Moments and Motions of a ship moving with a mean forward speed in six degrees of freedom are computed using Panel Method. In this study, an existing numerical model without speed consideration was modified by incorporating the speed parameters. Appropriate Green function was used to calculate the concern velocity potential. The accuracy of the developed numerical code employing the Panel Method has been validated by comparing the result with known/published results of a series 60 ship available in the literature. Based on the results presented in the paper, it can be concluded that the developed model is able to predict the responses of the ship with forward speed effect. Keywords: Motions, Green function, 3D Source distribution. Â  doi: 10.3329/jname.v1i1.2037 Journal of Naval Architecture and Marine Engineering 1(2004) 35-46